Invasive Nile tilapia Oreochromis niloticus (Linnaeus, 1758) in the Limpopo River system, South Africa : conservation implications - Chimimba, Christian Timothy (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.